Indicators for the Measurement of Teachers' Professional Identity across Asia and Africa: A Delphi Study. (December 2021) - Samsudin, Mohd Ali; Moen, Melanie Carmen; Hai, Pham Thi Thanh; Hagos Hailu, Belay; Hidayat, Arif; Ishida, Yoko; Kusakabe, Tatsuya; Ozawa, Hiroaki; Ishak, Nor Asniza; Malik, Shaik Abdul; Ismail, Bin Mohamed; Owoyemi, Toyin Eunice; et al.
The comprehensiveness of teacher professional identity (TPI) studies conducted by African and Asian researchers highlights the importance of valid TPI indicators across Africa and Asia. Questionnaire TPI indicators are important to obtain valid direct comparisons between teachers in Africa and Asia. The process of developing a questionnaire served as an avenue for researchers from Asian and African regions to learn about TPI pointers from each other. This study used the Delphi technique to achieve consensus on valid TPI indicators across African and Asian regions. Fourteen researchers from the Asia-Africa University Dialogue Network for Educational Development (AAD) were selected using purposive sampling. TPI in this study is defined as a multifaceted concept comprising contextual and personal factors that differ across national borders. The indicators in the questionnaire represented personal, social and institutional factors perceived by teachers and outlined in the literature. In the Delphi study process, the researchers used three rounds to validate the initial 40-item TPI questionnaire. Subsequent analysis of the results indicated high importance and consensus among experts. Owing to its standardized procedure, the TPI questionnaire makes it possible to collect and compare the TPI dimensions from the different socio-economic contexts in which teachers work in Africa and Asia. The findings of this study guide African and Asian researchers on the common understanding of TPI characteristics prevalent across African and Asian regions. Research protocols for fostering quality research toward addressing challenges faced by the teacher education sector in African and Asian countries is also implied.